Empowerment of CIRC Model in Building Competency Writing Prosa-Based Video - Sugiarti, Dewi; Rahman, Rahman; Sopandi, Wahyu; Sujana, Atep (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
Writing skills are one of the most important skills that students must master in order to communicate indirectly. The research aims to determine the students ' competence in writing prose through the empowerment of video-based CIRC models. The method used is quasy experiments with the design of one group pre-test and post-test. The subject of research is the elementary school student of Cisitu district 5th grade Cisitu subdistrict, which consists of 25 students, consisting of 8 men and 17 female 17. The instrument used is observation and test. Observations were made to see the activities of learners when implementing a video-based CIRC model, while tests were conducted to gauge student competence in writing videobased prose. The data obtained consists of two types namely qualitative data and quantitative data. The quality data is by using the observation sheet of student activity, while the quantitative data is processed by